Study of Humoral Immunity against Coronavirus Infection COVID-19 in Vaccinated Individuals with Vaccines Available in the Republic of Belarus (Sputnik V (Gam-COVID-Vac), RF and Sinopharm (BBIBP-CorV), PRC) - K. S. Korsak; I. O. Stoma; E. V. Voropaev; O. V. Osipkina; A. A. Kovalev (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. Many countries around the world are developing effective vaccines against SARS-CoV-2. The measure of the effectiveness of the vaccination process has traditionally been antibody production. The frequency and intensity of adverse reactions is also an important factor in making a decision regarding a vaccine. This study presents the results of the evaluation of the formation of humoral immunity and the occurrence of reactions in response to the administration of Sputnik V (Gam-COVID-Vac), RF, and Sinopharm (BBIBP-CorV), PRC. Aim. Analyze immunogenicity and reactogenicity of COVID-19 vaccines used in the Republic of Belarus (Sputnik V and Sinopharm). Materials and methods. Evaluation of postvaccination immune response by enzyme immunoassay and differential enzyme immunoassay for class G immunoglobulins to S- and N-proteins SARS-CoV-2. Blood plasma of the study participants was used as biological material. Blood sampling was performed 3 times: immediately before the first vaccine dose, on day 42, and 6 months after the first vaccine dose. To evaluate the frequency and intensity of postvaccination reactions, study participants were questioned. Results. At 42 days after administration of both vaccines, antibody levels are rising, with a significantly higher quantitative IgG count for the Sputnik V vaccine. This trend is also observed 6 months after the first dose of both vaccines, both among those previously infected with SARS-CoV-2 and those without a history of COVID-19. The comparison of Sputnik V and Sinopharm vaccine groups in terms of IgG (BAU/ml) levels to S- and N-proteins revealed a statistically significant difference in IgG levels to S-protein: the Sputnik V vaccine group had significantly higher IgG levels to S-protein than the Sinopharm vaccine group (p = 0.0000196). The incidence of adverse reactions in this study was 45%. All reactions noted were mild to moderate in severity. The most common were soreness and redness at the injection site, elevated body temperature, and a combination of several reactions. The increased body temperature after vaccination was more common among those vaccinated with the Sputnik V vaccine. Conclusion. Compared to Sinopharm, Sputnik V vaccine produces higher antibody level. Adverse reactions were observed in both vaccinated groups. However, significant statistical differences were found with regard to fever in the Sputnik V vaccine group, which occurred more frequently.